The tempo of relationship progression among low-income couples () - Sassler, Sharon (2010)
This paper examines the factors associated with the tempo of low-income couples’ relationship progression into sexual involvement and coresidence. Data come from a recently-collected survey, the Marital and Relationship Survey (MARS) that obtained information from low- to moderate-income married and cohabiting couples. Over one-fifth of male and female respondents reported becoming sexually involved with their current partner within the first week of dating. Entrance into shared living was also quite rapid; about one-third of respondents moved in with their partner within 6 months. Furthermore, about two-thirds of married respondents initially cohabited with their partners. Indicators of family disadvantage accelerated entrance into sexual involvement and coresidence; these effects are more pronounced for women than men. Our results also suggest that the pace of relationship progression, into sexual involvement as well as shared living, has accelerated among unions formed more recently.